The Position of Ministerial Instructions in the Indonesian State Administration System on the Enforcement of Restrictions on Community Activities (PPKM) - Mukhtar Lutfi; Mukhlis Latif; Mutawalli, Muhammad (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2022)
This study discusses the position of ministerial instructions in the Indonesian constitutional system for the implementation of restrictions on community activities as a result of the widespread spread of the corona virus disease (Covid-19) in Indonesia. The government issues policies that limit community activities, as well as other directives. Although the policy is considered effective by the government, it must be in line with the prevailing laws and regulations in Indonesia. This research is a normative research that uses legal material collection techniques through library research methods and is described qualitatively. This study explains how the position of ministerial instructions in the Indonesian constitutional system, the legal basis for the Enforcement of Community Activity Restrictions (PPKM) to the legal politics of regulating the Enforcement of Community Activity Restrictions (PPKM). The conclusion of this study is that the PPKM policy is a formal policy that is flawed, because Article 8 paragraph (2) of Law Number 12 of 2011 is violated in the stipulation of legislation. Although there are formal defects in the training process, PPKM substantially has similar characteristics to PSBB, which is regulated in Law Number 6 of 2018 concerning Health Quarantine and Government Regulation Number 21 of 2020. So it can be said that the legal product for implementing PPKM does not conflict with the rules laid down. above or above. Based on Law Number 2 of 2014 concerning Regional Government, health is not the absolute authority of the central government. Therefore, local governments have the authority to determine and enact regional regulations that specifically regulate PPKM. Keywords: The Minister’s Instruction; Constitutional System; PPKM